Ascites with right heart failure in a dog: diagnosis and management - Kumar, Karlapudi Satish; Srikala, Devarakonda (Journal of Advanced Veterinary and Animal Research, 2014)
A female Labrador dog presented with a history of distended abdomen was subjected for clinical, physical, hemato-biochemical, eletrocardiographic, and ultrasonographic evaluations. Respiratory distress, weakness, fluid thrill on palpation of abdomen, cough, cyanotic tongue, and syncope were the significant manifestations. Elevated levels of creatine kinase, lactate dehydrogenase, alanine amino transferase, and alkaline phosphatase with normal blood urea nitrogen and creatinine were the common serum chemistry findings. Low voltage QRS complexes were the electrocardiographic abnormalities. Classical ground glass appearance of abdomen, and enlarged heart with increased sternal contact were the radiographic findings of abdomen and thorax. Ultrasonography of abdomen revealed floating viscera in the anechoic effusion with engorged and distended hepatic vasculature. 2-dimensional echocardiography revealed dilated right ventricle both on B- and M-mode. Further, insufficiency in mitral and tricuspid valves were recorded on pulsed and color flow Doppler. Hence, right heart failure due to ascites was confirmed, and the condition was successfully managed with losartas, spiranolactone, co-enzyme Q10 and tricholine citrate, and sorbitol. DOI: http://dx.doi.org/10.5455/javar.2014.a15 J. Adv. Vet. Anim. Res., 1(3): 140-144, September 2014